Road users with hearing loss and evaluation of tactile support systems - Birgitta Marie Thorslund (19774566) (2015)
Hearing loss (HL) is one of the most frequent sensory deficit in humans (Stevens et al., 2013), which might reduce traffic safety. The prevalence of age-related HL is increasing (Roth et al., 2001), and as a consequence the number of road users with HL will also increase. The effects of HL on traffic safety have been investigated and the use of tactile support systems has been evaluated both in a driving simulator and in real traffic. Tactile support was used to alert the driver during the simulator drive and to facilitate navigation with a GPS during the drive in real traffic. Differences related to HL in terms of driving behavior were bound to driving condition and occurred when complexity of driving task increased. There was also an effect of HL on visual behavior, indicated in the simulator and confirmed in the field study, suggesting that drivers with HL have a more active visual behavior with more frequent glances in the rear view mirror and a general scanning of the environment before looking away from road. Tactile signal in the driver seat was found useful, both for calling for driver attention and to facilitate navigation. Also, of high relevance for the traffic safety aspect and regardless of hearing status, the tactile support lead to higher satisfaction with the navigation system, less time spent to look at the navigation display, and thus more focus on road and better driving performance. The effects of HL on traffic safety consistently point towards a generally more cautious driving behavior. Compensatory strategies associated with HL include driving at lower speeds, more comprehensive visual search behavior and less engagement in distracting activities. Evaluation of a tactile signal suggests that by adding a tactile modality, some driver assistance systems can be made accessible also for drivers with HL. At the same time the systems might be more effective for all users, which could generally increase both traffic safety and mobility. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.38